(untitled) (Docentes 2.0 Journal, 2023)
Assessment can be a means of review and self-learning for the student and the teacher. However, it is often seen as a test of students’ knowledge rather than a learning strategy that guarantees the quality of teaching. Therefore, it became more evident during the COVID-19 health crisis, forcing teachers to look for new evaluation forms. Therefore, a topic of interest for an article whose objective was to analyze the main trends in the use of formative assessment strategies or suggestions in bilingual teaching during the pandemic. Research that used the deductive method was based on the positivist paradigm within a transversal quantitative research approach. A systematic review that applied content analysis as a technique supported by Prisma guidelines for the preparation of reviews on a sample of 16 articles from the last five years selected from different scientific journals indexed to the databases Scopus, Scielo, Web of Science, EBSCO, and Google Scholar. The results show the lack of research on bilingual formative assessment in the context of the COVID-19 pandemic. However, the education system’s global challenges require formative assessment strategies that provide feedback with descriptive and constructive comments that encourage critical thinking among all participants. In conclusion, bilingual formative assessment is an excellent strategy to enhance critical thinking skills in students.